After the lights go down - Hill, Donna (Donna O.) (Harlequin desire, 2023)
All is fair in love and war...and television morning shows! Two headstrong news anchors collide at the desk and in the bedroom in Donna Hill's latest! Two news anchors. One job. And a passion that won't be denied... It's lights, camera, scandal when competing morning show anchors Layne Davis and Paul Waverly set their sights on the same promotion. Yet sizzling looks and smoking hot kisses are proving more distracting than the competition itself. Paul has always been the object of Layne's desires, and now's her chance to close the deal. But will a future with Paul mean sacrificing her dream of having both a successful career and love?